2004
DOI: 10.1093/annonc/mdh470
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment of metastatic colorectal cancer with irinotecan, oxaliplatin and 5-fluorouracil/leucovorin (FOLFOXIRI): results of a phase II study with a simplified biweekly schedule

Abstract: This simplified FOLFOXIRI combination can be delivered easily in outpatient settings, with manageable toxic effects, and has very promising antitumor activity. While the safety profile seems to be improved in comparison with our previous FOLFOXIRI regimen, antitumor activity and efficacy appear to be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 26 publications
4
63
0
2
Order By: Relevance
“…In particular, a phase III study conducted by the GONO demonstrated the superiority of the first-line triplet FOLFOXIRI vs a standard doublet in terms of activity and efficacy. However, 5-FU had to be administered as a 48-h continuous infusion by a central venous catheter to make the combination feasible (Falcone et al, 2002(Falcone et al, , 2007Masi et al, 2004). Our report is the first multicenter phase II study evaluating the activity of a first-line triplet combination of irinotecan and oxaliplatin associated with capecitabine instead of 5-fluorouracil in the treatment of metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a phase III study conducted by the GONO demonstrated the superiority of the first-line triplet FOLFOXIRI vs a standard doublet in terms of activity and efficacy. However, 5-FU had to be administered as a 48-h continuous infusion by a central venous catheter to make the combination feasible (Falcone et al, 2002(Falcone et al, , 2007Masi et al, 2004). Our report is the first multicenter phase II study evaluating the activity of a first-line triplet combination of irinotecan and oxaliplatin associated with capecitabine instead of 5-fluorouracil in the treatment of metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a sequential strategy, 20 -50% of patients who progress after first-line chemotherapy cannot receive second-line treatment, mainly because of deterioration of their performance status and liver function (Grothey et al, 2004). Furthermore, another pooled analysis indicated that there is a strong correlation between the response rate to first-line chemotherapy and the possibility of a postchemotherapy radical resection of metastases that may be associated with long-term survival (Folprecht et al, 2005).Keeping these concepts in mind, the GONO group developed in phases I and II trials a triple-drug combination of oxaliplatin, irinotecan and 5-FU/LV named FOLFOXIRI (Falcone et al, 2002;Masi et al, 2004) and compared this combination to a standard doublet combination of 5-FU/LV plus irinotecan (FOLFIRI) in a phase III study on 244 mCRC patients (Falcone et al, 2007). The treatment with first-line FOLFOXIRI was feasible, associated with manageable toxicities and obtained a higher tumour response rate and a higher postchemotherapy radical resection of metastases rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a sequential strategy, one third of patients are not able to receive secondline therapy. Many phase I-II studies demonstrated the feasibility and promising activity of upfront biweekly 5-fluorouracil (5-FU) infusion combined with oxaliplatin and irinotecan [6,8]. A phase III study [9] comparing 5-FU, leucovorin, oxaliplatin, and irinotecan (FOLFOXIRI) with 5-FU, leucovorin, and irinotecan (FOLFIRI) demonstrated that FOL-FOXIRI produced manageable toxicities and led to a significantly higher RR (up to 60%), longer progression-free survival (PFS) time, and longer OS time.…”
Section: Introductionmentioning
confidence: 99%
“…As exposure to three active agents, rather than second-line therapy itself, appears to predict improved survival (Grothey and Sargent, 2005), 'up-front' administration of three effective drugs may be the most effective way to improve outcomes. Consequently, several groups have investigated the FOLFOXIRI combination (5-FU, oxaliplatin and irinotecan) in patients with mCRC (Masi et al, 2004;Souglakos et al, 2006;Falcone et al, 2007). Results from phase III studies have been conflicting, however, with Falcone et al (2007) demonstrating better outcomes for patients treated with FOLFOXIRI compared with FOLFIRI, and Souglakos et al (2006) reporting no significant difference between the two regimens.…”
mentioning
confidence: 99%